2018
DOI: 10.1002/mc.22897
|View full text |Cite
|
Sign up to set email alerts
|

TRIM59 overexpression correlates with poor prognosis and contributes to breast cancer progression through AKT signaling pathway

Abstract: TRIM59 has been recently implicated in the carcinogenesis of several cancers such as lung cancer, gastric cancer, and bladder cancer. However, its expression pattern and clinical significance has not been investigated in human breast cancer. In the present study, we examined TRIM59 protein expression in 95 cases of breast cancer tissues using immunohistochemistry. We found that TRIM59 was upregulated in 42 out of 95 cases and correlated with TNM stage (P = 0.0056), lymph node metastasis (P = 0.0088) and poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Furthermore, overexpression of TRIM44 enhanced the migratory and invasive abilities of the lung cancer cell lines A549 and H441 (34). Previous studies reported that TRIM59 was associated with the genesis, development and prognosis of tumors (12,15,35). For example, TRIM59 was upregulated and promoted cell proliferation, migration and invasion in human osteosarcoma (36).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, overexpression of TRIM44 enhanced the migratory and invasive abilities of the lung cancer cell lines A549 and H441 (34). Previous studies reported that TRIM59 was associated with the genesis, development and prognosis of tumors (12,15,35). For example, TRIM59 was upregulated and promoted cell proliferation, migration and invasion in human osteosarcoma (36).…”
Section: Discussionmentioning
confidence: 87%
“…A previous study revealed that upregulated TRIM59 served as a proto-oncogene and induced the progression of prostate cancer in transgenic mice (38). The upregulation of TRIM59 not only enhanced the expression of cyclin A, cyclin E, Bcl-xl, Bcl-2 and phosphorylated-AKT, and downregulated the expression of p21, p27 and p53, resulting in poor prognosis in breast cancer, but also affect breast cancer progression via the AKT signaling pathway (12). The aforementioned studies suggested that TRIM59 regulates a diverse range of cellular functions during tumor progression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Current research focused on the function of TRIM59 in various types of cancer and has demonstrated that TRIM59 can regulate the PI3K/AKT signal pathway in various cancers. TRIM59 promotes neuroblastoma through the Wnt/beta-catenin (24) and PI3K/AKT signaling pathways (18), accelerates bladder cancer via the TGF-beta/Smad2/3 signaling pathway (25), and facilitates breast cancer (26), cholangiocarcinoma (17,19), and ovarian cancer (27) through the PI3K/AKT signaling pathway. PI3K/AKT is also related to inflammation by activating IKKα and the whole NF-κB signal pathway (20).…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 Elevated TRIM59 expression is correlated with a relatively poor prognosis and progression in breast cancer. 30 Knocking down TRIM59 expression remarkably inhibits cell proliferation in neuroblastoma, 31 hepatocellular carcinoma, 32 and cholangiocarcinoma. 33 However, to date, the role of TRIM59 in retinoblastoma has not been reported.…”
Section: Discussionmentioning
confidence: 99%